Al-Qur'ān And The Humanization Of Women (Analysis Of Women's Rights And Position In The Verses Of The Qur'an) - Abdullah, Faisal; Hamzah, Ghufron (TAWASUT, 2024)
The Quran emphasizes the significant role of women in Islam and highlights their importance through various verses. It promotes equal treatment and opportunities for both genders, recommending education for women and acknowledging their crucial social contributions. Several Quranic verses discuss the rights and obligations shared equally by men and women, demonstrating that there is no inherent discrimination between them. Additionally, specific provisions within the Quran grant unique benefits to women during childbirth and childcare processes. Despite these principles of equality, some interpretations suggest limitations on women’s participation in public spheres. Ultimately, the Quran serves as a guiding framework for Muslims navigating contemporary challenges. This study employs a descriptive qualitative content analysis with thematic interpretation (Maudhu'i method) to analyze selected Quranic verses addressing similar topics. By examining these interconnected themes, we conclude that both sexes enjoy identical rights and roles; sometimes, women receive preferential treatment as evident from specific Quranic passages. While discussions around male responsibilities often focus on duties, those concerning females center on their entitlements. Keywords: Quran, Women, Rights, Equality